The Effect Of 10% And 30% Lavender Essential Oil Balm On Serum Cortisol Levels In Rats Given Stressor - Putra, Christian JS; Suyono, Handi; Jong, F.X Himawan H. (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Indonesian Ministry of Health published Basic Health Research stated that the incidence of stress in Indonesia increased between 2013 and 2018. Untreated stress is a riskfactor for suicide and can cause the onset of depression. Stress associated with cortisol, thishormone has many functions in our body, such as increasing blood sugar levels, reducinginflammation, and suppressing the immune system  One of the essential oils commonly used is English Lavender (Lavandula angustifolia). The lavender essential oil has many benefits, such as reduce anxiety, relieve pain, improve sleep quality, bactericidal, and repellent Purpose: This study aims to research the effectiveness of 10% and 30% lavender essential oil balm on serum cortisol levels in rats given stressor.  Method: This study used 37 male rats randomly divided into four groups: negative control, positive control, 10% lavender balm, and 30% lavender balm. The forced swim test was given as the stressor every day for ten days, 20 days, and 30 days. The lavender oil balm was pplied to the back after the forced swim test. ELISA Kit measured the serum cortisol levels. Results: The results showed that 10% lavender essential oil balm significantly (p=0.007 and p=0.041) decreased serum cortisol levels compared to negative control and positive control group. However, there was no statistically significant difference in serum cortisol levels in the 30% lavender essential oil group. Furthermore, there was no significant difference in serum cortisol levels between 10 days, 20 days, and 30 days of the 10% and 30% lavender essential oil balm.   Conclusion: The effectiveness of lavender essential oil balm to decrease the serum cortisol levels depends on the concentration and not depending on the duration of administration. 10% lavender essential oil balm lowers the serum cortisol levels more than 30% lavender ssential oil balm.